2011
DOI: 10.1039/c0cp02122a
|View full text |Cite
|
Sign up to set email alerts
|

Fez+ (z = 1–6) generation from ferrocene

Abstract: Multiply charged iron atoms up to Fe(6+) with few carbon ions were produced from ferrocene under intense femtosecond laser fields. The production of Fe(4+) and Fe(5+) from ferrocene requires much less laser intensity than theoretically expected for iron atoms. The dissociation of ferrocene and the generation mechanism of multiply charged iron atoms are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Mass spectrum of Fe(CO) 5 doped SF 6 clusters at 1,064 nm. & Nakashima, 2010;Yatsuhashi, Marukami, & Nakashima, 2011;Dota et al, 2012). This work demonstrates that even low intensity nanosecond laser pulses ($10 9 W/cm 2 ) can efficiently generate multiply charged atomic ions, upon irradiation of organometallic clusters.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Mass spectrum of Fe(CO) 5 doped SF 6 clusters at 1,064 nm. & Nakashima, 2010;Yatsuhashi, Marukami, & Nakashima, 2011;Dota et al, 2012). This work demonstrates that even low intensity nanosecond laser pulses ($10 9 W/cm 2 ) can efficiently generate multiply charged atomic ions, upon irradiation of organometallic clusters.…”
Section: Discussionmentioning
confidence: 76%
“…These two parameters can significantly affect the charge state as well as the total number density of the ions generated by the photoionization processes. The work of Yatsuhasi et al and Dota et al reports generation of multiply charged atomic ion (such as Si 4+ and Fe 6+ ) upon exposure of organometallic monomers to femtosecond laser pulses of intensity ∼10 15 W/cm 2 (Yatsuhashi & Nakashima, ; Yatsuhashi, Marukami, & Nakashima, ; Dota et al, ). This work demonstrates that even low intensity nanosecond laser pulses (∼10 9 W/cm 2 ) can efficiently generate multiply charged atomic ions, upon irradiation of organometallic clusters.…”
Section: Discussionmentioning
confidence: 99%
“…46 At comparable laser intensities to this work, Yatsuhashi et al found single ring loss to be around an order of magnitude less likely than double ring loss in the asymptotic limit of microsecond scale detection times. 19 The authors assumed that a sequential dissociation mechanism may account for the preference for double ring loss. The results presented here, however, suggest that the preference may instead be due to a very fast dissociation mechanism involving both rings, potentially because it is so easy to break the bond between the iron atom and the second ring.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yatsuhashi and co-workers have demonstrated that strong field ionization of gaseous FeCp 2 with a femtosecond NIR pulse yields multiply charged Fe n+ ions. 19 Using time-offlight mass spectrometry, the authors found that, as the NIR intensity is increased beyond 1 × 10 15 W cm −2 , Fe ions with charge states as high as Fe 6+ are observed. Intriguingly, dissociation leading to the loss of a single cyclopentadienyl ring was a minor channel compared to double ring loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation